Role of leukotriene antagonists and antihistamines in treatment of allergic rhinitis and asthma comorbidity - Baççıoğu, Ayşe; Yorgancıoğlu, Arzu; Cingi, Cemal; Çuhadaroğlu, Çağlar (ENT Updates, 2013)
Leukotriene receptor antagonists and antihistamines are efficient in reducing symptoms of allergic rhinitis and asthma when used alone or in combination. In patients with allergic rhinitis, H1-antihistamines prevent and relieve the sneezing, itching, rhinorrhea, and nasal congestion that characterize the early and the late response to allergen. H1-antihistamines are not medications of choice in asthmatic patients, but controlling rhinitis will improve asthma concomitantly. Leukotriene antagonist such as montelukast may be an alternative treatment for mild persistent asthma as monotherapy where inhaled corticosteroid cannot be administered or alternative to long-acting beta agonist as an add-on therapy to ICS for moderate to severe persistent asthma. Although montelukast is an effective drug in allergic rhinitis indicated as monotherapy, but widely recommended as adjunct to antihistamine or intranasal corticosteroid. Antileukotriene agents are also widely used in the treatment of pediatric asthma. In children, maintenance treatment with inhaled corticosteroids in pure episodic (viral) wheeze was ineffective, but maintenance as well as intermittent montelukast was shown to have an efficient role in both episodic and multi trigger wheeze. Furthermore, their advantage to inhaled corticosteroids is that leukotriene receptor antagonists do not affect short-term lower leg growth rate in prepubertal children.